STUDY OF PRINCIPAL LEADERSHIP IN INCREASING WELFARE THROUGH THE TEACHER'S DISCIPLINE AT SMK REGENCY OF BOGOR (CASE STUDY AT SMK NURUL HIDAYAH 1 AND SMK IBNU AQIL KABUPATEN BOGOR) - Hasan Basri; Sofyan Sauri; Achmad Mudrikah; Ricky Yoseptry (IJGIE (International Journal of Graduate of Islamic Education), 2022)
Teacher welfare is the success of leaders and the fulfillment of education. Leaders work with five criteria, namely planning, program, implementation, evaluation, constraints and solutions. The purpose of this study was to analyze the program, planning, implementation, evaluation as well as the constraints and solutions of principals in improving teacher welfare through discipline. This study uses a qualitative approach to the interactive inquiry model with descriptive methods and uses interview, observation and case study techniques. The results of the study indicate that the program is implemented by providing incentives for teachers who achieve discipline targets. The planning is through the preparation of a team of policy formats, formulating problems, analyzing the challenges faced by schools, supporting schools, and taking an inventory of decisions. Implementation according to the program, building communication, building a tiered coordination system, motivating and facilitating teachers in improving skills and being active in MGMP, facilitating infrastructure. infrastructure, leadership regeneration, supervision and collaboration with institutions outside the school. Evaluation through monthly formal activities and informal activities. Constraints of low teacher salaries, staffing status and limited facilities The solution is to apply teacher incentives